Hydrogeochemistry of Hot Springs and the 2018 Mojiang M 5.9 Earthquake-Related Chemical Changes in the Simao Basin, China - Li, Qilin; Zhao, Ciping; Wang, Yun; Zhou, Yiying; Ran, Hua (Frontiers in Earth Science, 2022)
The Simao Basin is characterized by strong tectonic activity and frequent seismicity. This study investigated the hydrochemical characteristics of 21 thermal springs in the Simao Basin from 2018 to 2020. In this study period, the 2018 Mojiang M5.9 earthquake caused several hydrochemical changes. The results indicate that the Simao Basin contained saline spring waters, HCO3−-rich spring waters, and SO42−-rich spring waters. In the study area, the water chemistry types were controlled by stratum lithology. Saline springs flowed through red beds and dissolved large amounts of halite, which is a rich source of Cl−and Na+ ions. In the hot spring waters, Ca2+ (Mg2+) and HCO3− were mainly derived from the dissolution of carbonate minerals, gypsum, and anhydrite of Triassic rocks. The higher SO42- content in the hot spring waters was caused by the pyrite present in Ailaoshan metamorphic rocks. The reservoir temperatures (121–289° C) in the Simao Basin were estimated by the silica-enthalpy mixing model equation and the silica-enthalpy diagram. The hot springs had higher reservoir temperatures (> 250° C) and were mainly located at the edges of the basin. Metamorphic rocks exposed in the region had low permeabilities and these springs was close to nearby deep faults that provided deep heat. In most springs, the concentrations of Ca2+ and HCO3− ions increased obviously before the 2018 Mojiang M5.9 earthquake; however, the concentrations of these ions decreased after the earthquake. The hydrogeochemical variations might be attributed to the vigorous water-rock interactions and the mixing of secondary fluids. The entry of cold shallow groundwater caused changes in the reservoir temperatures of some spring samples.